2016
DOI: 10.1037/dev0000182
|View full text |Cite
|
Sign up to set email alerts
|

Maternal scaffolding and home stimulation: Key mediators of early intervention effects on children’s cognitive development.

Abstract: This study contributes to the understanding of how early parenting interventions implemented in low- and middle-income countries during the first 2 years of children's lives are sustained longitudinally to promote cognitive skills in preschoolers. We employed path analytic procedures to examine 2 family processes-the quality of home stimulation and maternal scaffolding behaviors-as underlying mechanisms through which a responsive stimulation intervention uniquely predicted children's verbal intelligence, perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
108
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(123 citation statements)
references
References 51 publications
12
108
0
3
Order By: Relevance
“…Families in poverty have fewer financial resources to invest in enriching materials, resulting in inequalities in EF development across SES (family investment model; Conger & Donnellan, ); this may be exacerbated by “book deserts” observed in low‐income U.S. neighborhoods (Neuman & Moland, ), or reduced access to print in LMICs with many remote areas (Spaull & Taylor, ). However, these findings suggest an EF intervention target for low‐SES communities; an intervention program to offset the effects of poverty by providing cognitively stimulating environments has demonstrated positive effects on EF in children in Pakistan (Obradović, Yousafzai, Finch, & Rasheed, ). Such interventions can be applicable worldwide.…”
Section: Mediators and Moderators Of The Poverty–ef Link: Similaritiementioning
confidence: 99%
“…Families in poverty have fewer financial resources to invest in enriching materials, resulting in inequalities in EF development across SES (family investment model; Conger & Donnellan, ); this may be exacerbated by “book deserts” observed in low‐income U.S. neighborhoods (Neuman & Moland, ), or reduced access to print in LMICs with many remote areas (Spaull & Taylor, ). However, these findings suggest an EF intervention target for low‐SES communities; an intervention program to offset the effects of poverty by providing cognitively stimulating environments has demonstrated positive effects on EF in children in Pakistan (Obradović, Yousafzai, Finch, & Rasheed, ). Such interventions can be applicable worldwide.…”
Section: Mediators and Moderators Of The Poverty–ef Link: Similaritiementioning
confidence: 99%
“…This notion suggests that, generally speaking, the best time to intervene may be during young adulthood. However, some children, and even infants, may exhibit some (perhaps all) of these brakes [e.g., Obradović et al, 2016]. The ideas from our framework could be applied to both aging adults and typically developing younger learners, as well as perhaps learners with developmental disabilities.…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…More recent research has demonstrated how and when infants and children learn from people [e.g., Koenig & Sabbagh, 2013], as well as characterizing the nature of "scaffolding" and its effects in finer detail [Harris & Almutairi, 2016;van de Pol, Volman, & Beishuizen, 2010]. For disadvantaged children, a scaffolding intervention with the primary caregiver increases basic cognitive skills, as well as academic abilities [Obradović et al, 2016]. For adults, learning can often be self-paced or computerized, which may lead to some gains [e.g., Dunlosky et al, 2007;Mishra, de Villers-Sidani, Merzenich, & Gazzaley, 2014].…”
Section: Individualized Scaffoldingmentioning
confidence: 99%
See 1 more Smart Citation
“…Maternal cognitive stimulation, such as asking questions, naming objects, and giving directions, is also associated with 2‐year‐old toddlers' participation and responses during play (Valentino et al, ). Similarly, it has been demonstrated that responsive stimulation by mothers, such as sensitivity to the child, reinforces 15 to 24‐month‐old toddlers' executive functioning and cognitive and language development and encourages more engagement in complex play (Fiese, ; Obradović, Yousafzai, Finch, & Rasheed, ; O'connell & Bretherton, ). To our understanding, there is a dearth of research in Asian contexts examining the effects of maternal scaffolding on toddlers' active and joint engagement during play.…”
Section: Introductionmentioning
confidence: 99%